- Relevansi Klasifikasi Lesi Hemisfer Kanan dan Kiri dalam Memprediksi Gangguan Kognitif Pascastroke - Dienanta, Savira; Hamdan, Muhammad; Soetjipto, Soetjipto; Machin, Abdulloh (Majalah Kedokteran Indonesia, 2020)
Introduction: Stroke is the fifth leading cause of disability-adjusted life years (DALYs) in the world. Cognitive impairment is one of the disabilities found in the acute phase of stroke and persists in long-term outcomes which can be assessed using the Mini-Mental State Examination (MMSE). However, a clinical classification to predict the cognitive outcome remained unclear. This study is aimed to identify differences of MMSE results in stroke patients between right and left hemisphere lesions to ensure the mentioned location classifications may contribute to cognitive outcome prediction.Method: With the cross-sectional analytic observational design, 32 acute phase patients hospitalized in the Neurology Department Soetomo General Hospital from October–December 2019 were assessed using the Indonesian version of MMSE with purposive sampling and analyzed using the chi-square test.Result: There was no significant difference between MMSE scores in right or left hemisphere lesion. This might happen because (1) MMSE was insensitive and not a domain-specific test; (2) a more specific infarct location was needed to predict cognitive outcome post-stroke, including microarchitecture of the brain especially those involved in the cortico-striato-thalamocortical loop.Conclusion: The right or left hemisphere lesion classification did not contribute significantly to predict cognitive impairment.